Análise do modelo input-output-outcome do processo de inovação de produto e processo na indústria brasileira de transformação - Ishizaka, Artur Yuiti (Universidade Federal de São Carlos, 2019)
This dissertation sought to analyze the relationship between the inputs and outputs of the product and process innovation process, and its impacts on the performance of firms, through the application of a Partial Least Squares Structural Equation Modeling (PLS-SEM), using data from the Innovation Survey 2014 (PINTEC). The main variables of inputs, outputs and outcomes of innovation were identified in the literature through a systematic literature review, and a research model was proposed. Constructs of internal (internal-to-company resources) and external inputs (acquisitions), product and process outputs, and outcomes related to products, market share, and business processes were used. The application of PLS-SEM allowed the evaluation of the composition of each construct, relationships between them and impacts of control variables of firm size and technological intensity of the companies in the proposed model. All relationships between constructs were confirmed as positive, except for the relationships between external inputs and product outputs and between product outputs and outcomes related to productive processes, which presented negative relationships. Also, a distancing between the processes of product and process innovation was noticed, evidencing the lack of integration between them. The impact of the size and technological intensity of the companies were significant for some of the model relationships. The control variable of firm size evidenced mainly the greater capacity of larger companies in dealing with the parallel development of innovations of product and process. As for the technological intensity variable, it showed that companies of low technological intensity tend to benefit more from product and process innovations in terms of product and market share outcomes.
Product and process innovation input-output-outcome model analysis in the brazilian manufacturing industry
Keywords: Processo de inovação; PINTEC; Inputs da inovação; Outputs da inovação; Outcomes da inovação; Innovation process; Innovation inputs; Innovation outputs; Innovation outcomes; ENGENHARIAS::ENGENHARIA DE PRODUCAO